Evaluation of the relationship between air pollutants and emergency department admissions with childhood asthma - Söğütlü, Yakup; Altaş, Uğur; Altıntaş, Tuğba; Altaş, Zeynep Meva; Akova, Sevgi; Özkars, Mehmet Yaşar (My University, 2024)
Background: This study aims to evaluate the relationship between the number of visits to a pediatric emergency department due to asthma attacks and air pollutants. Methods: In this ecological study, all pediatric patients who visited the pediatric emergency department of a tertiary hospital in Istanbul with asthma between January 2016 and December 2023 were included. The effect of air pollution on the number of patient visits was analyzed using a negative binomial regression model. Results: Based on the negative binomial model, a one-unit increase in SO2 leads to a 0.020-unit decrease in the logarithm of the number of patient visits (p < 0.05). A one-unit increase in NO leads to a 0.040-unit increase in the logarithm of the number of patient visits (p < 0.05). According to factor analysis, as the levels of NO, NOx, PM2.5, NO2, and PM10 in the air increase, the number of patient visits also increases; however, as the level of SO2 increases, the number of patient visits decreases. Conclusions: Families should be informed about environmental exposures for disease management of children with asthma. The confounding factors may also play a role in SO2 level and the decrease in admissions due to asthma. Further studies are needed in this regard.
Keywords: Air Pollutants; Asthma; Children; Emergency Department